El enoturismo en las Islas Baleares visto por las bodegas - Ramón Cardona, José; Vachiano Pol, Marga; Serra Cantallops, Antoni (Tourism and Hospitality International Journal, 2023)
The Balearic Islands have been seeking to deseasonalise and diversify tourism activity for decades. One of the options that have been considered is wine tourism, mainly due to the increase in the number of existing wineries. Wine tourism has been a growing field of study since the 1990s, with a considerable amount of literature in the regions of the New World. In the Balearic Islands, academic studies have traditionally focused on the supply and demand of sun and beach tourism, with few studies on alternative or minority tourism offers. This paper aims to make a first approximation to the situation of wine tourism in the Balearic Islands, through a study of the wineries. This study allows us to show their vision of wine tourism. Wine tourism has little impact on the economy as a whole, but it is useful for the wineries, improving their income and exports. The profile of wine tourists is similar to that of sun and beach tourists, with a predominance of foreigners. In the future, wine tourism will be focused on complementing other tourist offers and supplementing the wineries' income.